KEBIJAKAN PEMERINTAH PADA MADRASAH ALIYAH NEGERI INSAN CENDEKIA (MAN IC) - Ismail Ismail; Sumarmi Sumarmi; Muchammad Eka Mahmud (Damhil Education Journal, 2023)
Government policy in terms of education is one of the tools to create a condition that meets the expectations and goals of education itself. And MAN IC is an educational institution based on religiosity and science and technology which has the goal of creating a generation that is faithful and intelligent in general science in order to realize the ideals and goals of education, especially in Indonesia. This study aims to describe how the policies of the Ministry of Religion of the Republic of Indonesia at Madrasah Aliyah Negeri Insan Cendekia (MAN IC). Apart from that, this research also looks at the extent to which the policy implementation by the Ministry of Religion of the Republic of Indonesia for Madrasah Aliyah Negeri Insan Cendekia (MAN IC). This study uses a qualitative research method with a literature study approach. The technique of reading various literature or journals related to government policies at Madrasah Aliyah Negeri Insan Cendekia (MAN IC) is a technique in collecting data in this research. The results of the research show that the government, in this case, namely the Ministry of Religion of the Republic of Indonesia has the right and authority in administering Madrasah Aliyah Insan Scholars as stated in the Decree of the Minister of Religion of the Republic of Indonesia No. 744 of 2017 concerning the establishment of MAN IC. In addition, the aim of organizing MAN IC is to increase access and quality in superior madrasa education services that have verified academic and non-academic reinforcement. And in PMA No. 66 of 2016 it is explained that the Ministry organizes at least one MAN IC in each province